New Sounds, New Stories Narrativity in Contemporary Music - Meelberg, Vincent (LUP Dissertaties, 2006)
When listeners talk about their listening experiences, they often refer to music as if it were a narrative. But can music actually tell a story? Can music be narrative? Traditionally, narrativity is associated with verbal and visual texts, and the mere possibility of musical narrativity is highly debated. In this study, Vincent Meelberg demonstrates that music can indeed be narrative, and that the study of musical narrativity can be very productive. Moreover, Meelberg even makes a stronger claim by contending that contemporary music, too, can be narrative. More specifically, Meelberg suggests considering contemporary musical narratives as metanarratives, i.e. narratives that tell the story of the process of narrativization.